Indonesia's low concern for labour issues - Cahaya, F.; Porter, Stacey; Tower, G.; Brown, Alistair (Emerald Group Publishing Ltd, 2012)
Purpose: This study aims to advance explanations of the communication level of labor disclosures of Indonesian listed companies. Design/methodology/approach: Year-ending 2007 Annual report disclosures of 223 Indonesia Stock Exchange (IDX) listed companies are analyzed. The labor practices and decent work disclosure component of the 2006 Global Reporting Initiative (GRI) guidelines are used as the benchmark disclosure index checklist. Findings: The results show a low level of voluntary disclosure (17.7 per cent). The highest level of communication is for issues related to skills management and lifelong learning programs for employees. Very few companies disclosed information about health and safety committee and agreements, and salary of men to women. Statistical analysis reveals that government ownership and international operations are positively significant predictors of ‘‘labour’’ communication. Isomorphic institutional theory partially explains the variability of these disclosures. Bigger companies also provide more labor practices and decent work disclosures. Research limitations/implications: The main implications of the findings are that Indonesian companies are not clearly communicating labor responsibility issues as a key precondition of corporate social responsibility (CSR). They may be obfuscating some information to protect their image and reputation. Originality/value: This paper provides insights into the disclosure practices of labor issues, a specific social disclosure theme which is rarely examined in prior literature, under the umbrella of institutional theory. The research also includes ‘‘goal factor’’ to be tested as one of the independent variables.